Meristem-tip culture and virus indexing of sweet potatoes - Love, S.L.; Rhodes, B.B.; Moyer, J.W.; International Board for Plant Genetic Resources (1987)
This book collects the available technical data on in vitro methodology appropriate to sweet potato and looks at the problem of obtaining virus-free germplasm for distribution and conservation.